Food Grade Ehanol Production With Fermentation And Distillation Process Using Stem Sorghum - Yuliana Setyowati; Aniendia Candra Suminta; Tri Widjaja; Setiyo Gunawan (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2015)
10% -12% of sugar in its stem which is the optimum sugar concentration in fermentation process for bioethanol production. Sorghum has a high potential to be developed as a raw material for food-grade ethanol production which can be used to support food-grade ethanol demand in Indonesia through a fermentation process. This research focused on the effect of microorganism varieties in the fermentation process which are mutant Zymomonas mobilis (A3), Saccharomyces cerevisiae and Pichia stipitis mixture. The Research for purification process are separated into two parts, distillation with steel wool structured packing and dehydration process using molecular sieve and eliminating impurities using activated carbon. The research can be concluded that the best productivity shown in continuous fermentation in the amount of 84.049 (g / L.hr) using the mixture of Saccharomyces cerevisiae and Pichia stipitis. The highest percentage of ethanol yield produced in batch fermentation using the mixture of Saccharomyces cerevisiae and Pichia stipitis that is equal to 51.269%. And for the adsorption, the best result shown in continuous fermentation by using Zymomonas Mobilis of 88.374%..